GOVERNMENT DEBT SUSTAINABILITY: THE LITHUANIAN CASE - Kregždė, Arvydas (Ekonomika, 2012)
The paper deals with some aspects of sustainability of the government debt of Lithuania for a long, medium and short time horizon. The purpose of the study is to investigate the sustainability of the debt with respect to the nominal GDP growth, the interest rate on the debt, and the primary budget deficit. The differential equations calculus technique is used for the analysis of the debt. A scenario approach is used to simulate the sensitivity of the debt to economic shocks. An inequality for a non-increasing debt over a medium term is applied for the possibility to restore the level of the debt to a pre-crisis level. The sensitivity of the debt to a short movement of interest rate, the GDP growth rate and the primary budget deficit is investigated. A rule of debt change in a short run by one percentage point is formulated.